In and Out of Sight: The Afterlife of Official Photography from Idi Amin’s Uganda - Vokes, Richard (Kronos: Southern African Histories, 2021)
This article examines the output of Uganda’s official Photographic Section from the years of the Idi Amin regime (1971–9), an archive of 60,000 black and white images from which have recently come to light in the stores of the Uganda Broadcasting Corporation in Kampala. Drawing on recent developments in African visual studies, the article focuses in particular upon what this archive reveals about photographic circulations in and from Amin’s Uganda. It finds that this new trove of negatives – when compared with press archives from around the world – is especially revealing of a growing nexus between official photography and all kinds of commercial photographies in the 1970s. This nexus played a key role in shaping both how the Amin regime was pictured at the time, and how its afterlife has continued to reflect down to the present time.